Uneven Demographic Changes as a Challenge to Provide Access to Education in the Rural Areas in Poland - Wojewódzka-Wiewiórska, Agnieszka; Stawicki, Maciej (European Journal of Sustainable Development, 2020)
Dynamic changes in the number of inhabitants of rural areas in Poland entail necessity to adjust the market of public services and determine the way they are provided. In practice the intensity of this process varies both interregional and intra-regional. The objective of the study was to present how the uneven demographic changes including number of children affect organization of primary education by rural municipalities in selected Polish region. Research tasks were to present spatial diversity of demographic changes and number of pupils and schools and to identify and classify the ways of organization of education by rural municipalities depending on demographic processes. Research used data provided by Central Statistical Office for period 1998-2017. Moreover, data collected in own research (interviews conducted in 2018 and 2019) allowed to recognize public education services perception by local governments and rural society. Keywords: demographic changes; public services; schools; rural society; Poland